The Influence of Community Participation and Government Transparency on Policy Quality in the Bengkulu City Government - Romdana; Riski Kusuma Bakti (CV. Era Digital Nusantara, 2026)
This study aims to analyze the influence of public participation and government transparency on the quality of public policy at the Governor’s Office of Bengkulu City. A quantitative associative approach was used, with data collected from 63 civil servants through questionnaires and document analysis.The results show that both public participation and government transparency significantly affect policy quality, both partially and simultaneously. Citizen involvement in policy planning and evaluation increases the relevance and legitimacy of policy decisions. Transparency, through open access to information and accountability mechanisms, enhances public trust and policy effectiveness. The study is limited by its focus on civil servant respondents, without including perspectives from the general public. Therefore, it is recommended that the local government strengthen participatory mechanisms and digital transparency systems to support more inclusive, accountable, and high-quality policymaking.